A Fresh Look at Fiscal Redistribution and Inequality in the US across Electoral Cycles - Hector Sala (Institute of Labor Economics (IZA), 2018)
The evolution of the ratio of direct taxation (characterized by progressive rates) over indirect and payroll taxation (characterized by flat rates) is examined together with its distributional consequences for the Bottom 50%, Middle 40% and Top 10% shares of income. Oscillations of this ratio coincide with the US electoral cycles since the 1960s. We show that periods in which this ratio increases coincide with those in which Democrats rule the government and there is more redistribution from the rich (the Top 10%) to the rest of the population. Conversely, periods in which this ratio falls and Republicans hold the power are characterized by a fall in the ratio and less redistribution from the rich to the rest of the population. Based on a set of counterfactual simulations, we hypothesize that the rich, as informed economic agents, are able to protect themselves against tighter fiscal conditions, thereby curtailing the redistributive effects of enhanced tax progressivity.
Keywords: H20; H31; E25; 330; electoral cycles; tax composition; income distribution; tax progressivity